Investigation of yield and yield components of rapeseed (Brassica napus ssp. oleifera L.) genotypes in Trakya Region conditions (Revista de Investigaciones Universidad del Quindío, 2022)
The genotype*environment interaction was investigated in terms of yield and yield components of rapeseed varietys and candidate varietys depending on the years the research was carried out in Tekirdağ conditions. This research; In 2014-2015 and 2015-2016, 9 rapeseed cultivars and cultivar candidates were carried out in Tekirdağ location with 4 replications according to the Randomized Complete Block Design. In the analysis of variance, significant differences were found at the level of P < 0.01 and P < 0.05 in terms of yield and yield components in terms of genotype, year and year*genotype interaction statistically. According to the results of the analysis, the average yield of the genotypes varied between 2854-5356 kg ha-1, and the average of the years ranged between 3356-5121 kg ha-1. NK Caravel, candidate 1 (DK Ekstorm), candidate 3 (DK Expower) and candidate 4 (NK Linus) varieties have come to the fore in rapeseed cultivation in Tekirdağ conditions. The best results in terms of seed yield and yield components were obtained from NK Caravel, candidate 4 (NK Linus) and PR44W29 varietys. As a result, year, genotype and year*genotype interactions were examined in terms of yield and yield components of cultivars in rapeseed cultivation, and it was concluded that NK Caravel, candidate 4 (NK Linus) and PR44W29 cultivars showed high performance in Tekirdağ conditions, and the effect of the environment was higher than the effect of genotype.
Keywords: Rapeseed; yield; yield components; Interaction; Tekirdağ